CLUSTER ANALYSIS OF THE PATHOGENETIC RELATIONSHIPS OF METABOLIC PARAMETERS IN PATIENTS WITH NON-ALCOHOLIC FATTY LIVER DISEASE ON THE BACKGROUND OF HYPERTENSION (World Science, 2019)
The aim of the study was to conduct a cluster analysis of pathogenetic relationships between metabolic parameters, endothelial lipase levels, the severity of steatosis, and clinical parameters in patients with non-alcoholic fatty liver disease with hypertension. To analyze pathogenetic relationships, a cluster analysis was performed with the distribution of parameters into 4 clusters using the Ward's method. The most dense metabolic link by cluster analysis endothelial lipase forms with NAFLD liver fat score (2.639 cu), HbA1C (2.084 cu), total cholesterol (2.272 cu), and alcohol units (2.797 cu).